Evaluation of the possibilities of creating interference-resistant codes by selecting code word combinations - Hilgurt, S.Ya.; Davydenko, A.M. (Problems of Informatization and Management, 2025)
The work is devoted to the issues of finding the best codes capable of correcting the maximum possible number of errors for a given dimension. It is proposed to carry out such work by searching for possible combinations of code words using high-performance computing equipment. The main theoretical provisions are substantiated. Full and simplified algorithms are proposed that implement the method of building up, which allows improving the clarity and to significantly increase the speed of the algorithm, while losing accuracy not worse than the unit value of the maximum code distance. Approximate estimates of the memory and computation time required for the execution of the algorithm are given, which will be useful during the further implementation of the algorithm on high-performance computing devices. An upper estimate of the required computational resources of two main types is found – the amount of memory and machine time, as functions of the dimensionality parameters of the noise-resistant code.